Purification, characterisation and antioxidant activities of chondroitin sulphate extracted from Raja porosa cartilage. (1st August 2020) - Zhou, Chang; Mi, Si; Li, Jiao; Gao, Jie; Wang, Xianghong; Sang, Yaxin
Highlights: Chondroitin sulfate was isolated from Raja porosa cartilage with a yield of 36.51 %. The purity of 94 % indicated the adequation of RPCS for nutraceutical production. Considerable CS-C units (65.84 %) made RPCS a practical resource of 6-sulfated CS. RPCS exhibited higher in vitro antioxidant activities than shark CS. Abstract: This study was designed to isolate (isolation yield of 36.51 %) and characterise chondroitin sulphate (CS) from skate ( Raja porosa ) cartilage. Gel permeation chromatography demonstrated that the Raja porosa chondroitin sulphate (RPCS) obtained was a relatively uniform polysaccharide with a molecular weight of 40, 752 Da and a purity of 94.0 %. Fourier-transform infrared, nuclear magnetic resonance spectroscopy and strong anion-exchange high-performance liquid chromatography indicated that the content of the predominant GlcA-GalNAc6S unit in RPCS was 65.84 %, which was higher than that in shark CS (53.93 %). Furthermore, RPCS displayed more effective free radical scavenging effects than did shark CS, indicating the potential of RPCS to promote oxidative stress resistance and to act as an antioxidant agent. Skate cartilage could be exploited as a sufficient and sustainable source for the preparation of CS with higher 6S-sulphation, which in turn could be scaled up for use in the pharmaceutical industry.